DERIVING INTERNAL WAVE PHASE SPEED IN THE ARCTIC OCEAN FROM SEQUENTIAL SPACEBORNE SAR OBSERVATIONS - I. E. Kozlov; T. V. Mikhaylichenko (The International Archives of the Photogrammetry, Remote Sensing and Spatial Information Sciences, 2023)
Here we present direct estimates of phase speeds of short-period internal waves (SIWs) in the Arctic Ocean obtained from the analysis of sequential Sentinel-1 A/B SAR images. Analysis of the data near Svalbard in June-September 2018 has shown a peak in SIW observations in August. Three key regions of SIW generation are identified: deep Fram Strait, southern and central parts of Yermak Plateau and shelf regions northwest of Svalbard. Maximal SIW phase speed values are found over the Yermak Plateau and attain 0.84 m/s. Over Fram Strait and on the Svalbard shelf, phase speed values are similar with mean value about 0.2–0.3±0.03 m/s. We note that obtained SIW phase speeds are higher than maximal tidal currents over all three SIWs’ observation sites, suggesting their tidal generation and free propagation at subcritical Froude numbers. Comparison of the satellite-based phase speed estimates with theoretical values obtained using a two-layer model and actual hydrology shows a good correspondence for the cases when the time lag between the satellite and the field data is not exceeding one day.